2007
DOI: 10.1242/dev.001164
|View full text |Cite
|
Sign up to set email alerts
|

Different Wnt signals act through the Frizzled and RYK receptors duringDrosophilasalivary gland migration

Abstract: Guided cell migration is necessary for the proper function and development of many tissues, one of which is the Drosophila embryonic salivary gland. Here we show that two distinct Wnt signaling pathways regulate salivary gland migration. Early in migration, the salivary gland responds to a WNT4-Frizzled signal for proper positioning within the embryo. Disruption of this signal, through mutations in Wnt4, frizzled or frizzled 2, results in misguided salivary glands that curve ventrally. Furthermore, disruption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
43
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 50 publications
1
43
0
Order By: Relevance
“…Thus, catalytically active SFKs can synergize with limiting levels of DRL to induce commissure switching, and presumably act to control the wild-type trajectories of the AC axons. Furthermore, Src64B and drl have previously been reported to interact genetically during pupal brain development (Nicolai et al, 2003) and it was also recently reported that drl genetically interacts with the SFK genes to control salivary gland migration (Harris and Beckendorf, 2007).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Thus, catalytically active SFKs can synergize with limiting levels of DRL to induce commissure switching, and presumably act to control the wild-type trajectories of the AC axons. Furthermore, Src64B and drl have previously been reported to interact genetically during pupal brain development (Nicolai et al, 2003) and it was also recently reported that drl genetically interacts with the SFK genes to control salivary gland migration (Harris and Beckendorf, 2007).…”
Section: Discussionmentioning
confidence: 96%
“…Similar levels of suppression are observed in embryos heterozygous for drl or porc, established members of the Wnt5/drl signaling pathway. The other Drosophila SFK, SRC42A, which is also expressed in the embryonic CNS (Takahashi et al, 2005), plays partially redundant roles to those 2283 RESEARCH ARTICLE SFK requirement in Wnt/RYK signaling of SRC64B in other tissues (Takahashi et al, 2005;Tateno et al, 2000;Harris and Beckendorf, 2007). Heterozygosity for Src42A did not suppress the Wnt5 midline glial expression phenotype, possibly because SRC42A is not limiting under these conditions.…”
Section: Discussionmentioning
confidence: 98%
“…Likewise, distinct Wntsignaling pathways were shown to have opposing roles in tail fin regeneration (Stoick-Cooper et al 2007). In Drosophila, an attractive wnt4/fz and a repulsive wnt5/ryk signal together control salivary gland migration (Harris and Beckendorf 2007). As such, multiple Wnt pathways might collaborate in controlling complex morphogenetic events, by each regulating different aspects of cell polarization and directional migration.…”
Section: Discussionmentioning
confidence: 99%
“…Although inhibition of the canonical Wg pathway has a much more dramatic effect on cardiogenesis than lack of DWnt4, our data still leave the option that DWnt4 may also act through the canonical pathway. Despite several publications that indicate that DWnt4 activates a noncanonical pathway, Harris and Beckendorf (2007) concluded from their data that DWnt4 acts through a canonical Wnt pathway during salivary gland migration. PKCs were shown to mediate noncanonical Wnt signaling in vertebrates (Kühl et al, 2000;Winklbauer et al, 2001) and implicated in mediating the DWnt4 signal during ovarian morphogenesis (Cohen et al, 2002).…”
Section: Discussionmentioning
confidence: 96%
“…It is intriguing to hypothesize that DWnt4 acts as a guidance cue (attractive or repulsive) for the alary muscle attachment site. A guidance function for DWnt4 has been previously described in the context of dorsoventral projections of retinal axons of motor neuron target specificity and in salivary gland migration (Harris and Beckendorf, 2007;Inaki et al, 2007;Sato et al, 2006).…”
Section: Discussionmentioning
confidence: 97%